The soliton solution of a modified nonlinear schrÃ¶dinger equation - Zhang, Jumei; Yin, Li (Global Journal of Mathematical Analysis, 2017)
Hirota bilinear derivative method can be used to construct the soliton solutions for nonlinear equations. In this paper we construct the soliton solutions of a modified nonlinear SchrÃ¶dinger equation by bilinear derivative method.